Understanding the Design of Rural Agricultural Development Projects: The Case of Climate-Smart Villages in Kenya - Yang, Geneva Juanyu (Université d'Ottawa | University of Ottawa, 2024)
In the face of climate change-induced disasters that reduce crop yields and threaten farmer livelihoods, many development agencies started endorsing climate-smart agriculture (CSA) as the agricultural best practice in a warming world. The Climate-Smart Villages (CSV) in Nyando, Kenya are a participatory, outcome-focused agricultural research for development project that developed a series of tailored CSA interventions that have been shown to improve productivity, farmer adaptation, and greenhouse gas mitigation. Through systematic literature review and key informant interviews, this research paper first identified factors that enabled or constrained the project’s effectiveness: community engagement; local and national partnerships; capacity building; providing agricultural resources; incorporating gender considerations; monitoring and evaluation; outreach targeted at marginalized members; prioritization of project outcomes; and an integrated articulation of a theory of change. Next, the research paper contextualized the project in, and compared it with, historical and contemporary rural agricultural development projects in Kenya. By learning from the design and implementation of projects such as the Nyando CSVs, policymakers and development practitioners can maximize project outcome across multiple dimensions in the context of climate change. This case study provides a critical examination of best practices which can be further tested and applied. Keywords: climate-smart agriculture; rural development; climate change; Kenya